Global Existence and General Decay of Solutions for a Quasilinear System with Degenerate Damping Terms. (30th June 2021) - Ekinci, Fatma; Pișkin, Erhan; Boulaaras, Salah Mahmoud; Mekawy, Ibrahim
Abstract : In this work, we consider a quasilinear system of viscoelastic equations with degenerate damping, dispersion, and source terms under Dirichlet boundary condition. Under some restrictions on the initial datum and standard conditions on relaxation functions, we study global existence and general decay of solutions. The results obtained here are generalization of the previous recent work.